2016
DOI: 10.1002/anie.201602764
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Wide‐Band‐Gap Oxide Semiconductors with Cobalt Hydroxide Nanoclusters for Visible‐Light Water Oxidation

Abstract: Cobalt-based compounds, such as cobalt(II) hydroxide, are known to be good catalysts for water oxidation. Herein, we report that such cobalt species can also activate wide-band-gap semiconductors towards visible-light water oxidation. Rutile TiO2 powder, a well-known wide-band-gap semiconductor, was capable of harvesting visible light with wavelengths of up to 850 nm, and thus catalyzed water oxidation to produce molecular oxygen, when decorated with cobalt(II) hydroxide nanoclusters. To the best of our knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 51 publications
(104 reference statements)
3
40
0
Order By: Relevance
“…Various kinds of strategies have been proposed to improve separation and transfer efficiency of the photogenerated charges, among which fabrication of phase junctions is an effective approach. [9][10][11][12] The phase junctions in polymorph semiconductors, such as the anatase/rutile phase junction in TiO 2 [2,[13][14][15][16][17][18][19][20] and α/β phase junction in Ga 2 O 3 [21][22][23][24][25] have been widely investigated. This kind of phase junction constructed by the different phases of the same semiconductor has attracted much attention due to its simplicity, controllability and great photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of strategies have been proposed to improve separation and transfer efficiency of the photogenerated charges, among which fabrication of phase junctions is an effective approach. [9][10][11][12] The phase junctions in polymorph semiconductors, such as the anatase/rutile phase junction in TiO 2 [2,[13][14][15][16][17][18][19][20] and α/β phase junction in Ga 2 O 3 [21][22][23][24][25] have been widely investigated. This kind of phase junction constructed by the different phases of the same semiconductor has attracted much attention due to its simplicity, controllability and great photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the first‐row transition‐metal‐based catalysts, especially Co, Ni, and Fe‐based materials, have attracted extensive attention and been developed as promising electrocatalysts for OER in alkaline media . Moreover, the Co‐based materials have also been reported to act as excellent catalysts for photo/electrocatalytic water oxidation . Nevertheless, for OER in alkaline media, the corrosion of high‐concentration alkaline electrolyte hinders their large‐scale practical applications .…”
mentioning
confidence: 99%
“…Afterward, cobalt oxide or hydroxide has been widely used as the effective cocatalyst for photocatalytic water oxidation. [68][69][70] Hisatomi et al [68] demonstrated the activa tion of BaNbO 2 N by loading a CoO x cocatalyst for photocatalytic O 2 evolution under visible light. The BaNbO 2 N semiconductor has a small bandgap energy of 1.7 eV, allowing light absorption up to 740 nm, which can meet the requirement of 600 nm for sustainable solar water splitting.…”
Section: O 2 Production From Watermentioning
confidence: 99%